Illocutionary Act in Anger Management Movie - Feky Ega Situmorang; Nurma Dhona Handayani (Institut Agama Islam Negeri Palopo, 2020)
The purpose of the research was to find out the types of illocutionary act on Anger Management movie written by David Dorfmann. The data of this reserach were taken through observational method. The technic of the research used non-participatory. It was a descriptive qualitative research. The data analyzed used the theory of Searle and Austin. The result of this research there were 20 data utterances of illocutionary acts. The data was 8 showed directives, 1 showed assertives, 2showed commisive, 5showed declarative, 4and showed expressive. The data were consisted of five types: directives, assertives, commisives, declarative, and expressives. From all the data, the most used type of illocutionary acts was data for directive. The reason was because some people wanted to describe their feeling through their expression and people also liked to asked people not to do or do something by using directive illocutionary act.